ENGLISH VARIETIES USED IN INDONESIAN PRODUCT ADVERTISEMENTS - Sisila Fitriany Damanik (BAHAS, 2011)
Advertisement is communicated through some media by many industries by using persuasive and informative languages to attract or direct the consumers to buy the products. In line with the advancement of the English varieties in Indonesia, the language used in the product advertisements is not only Indonesian language, but English as a foreign language is also used by the copywriters of the product advertisement to persuade the consumers. This paper explains and describes English varieties used in some Indonesian product advertisements. The English varieties are observed from the study of words in view of pronunciation, spelling, simple phrases and grammar. Key words: English varieties, product advertisement, pronunciation, spelling, simple phrases, grammar.